Características en el diseño de la política económica local de Yucatán. ¿Se puede considerar política pública? - Rodríguez Cedillo, Gabriel Alejandro (2025)
Objetive: This paper attempts to awaken a renewed discussion of public policy’s design and orchestration from local frame, but on focusing on public policy. It considers the people involvement on public affairs in a delimitated area could provoke a positive influence on economic policy design and orchestration. Henceforth, the proposal of this paper is focused on design and orchestration of Yucatan’s economic policy and its recognition as a form of public policy. Methodology: The procedure used is documentary research that can provide a qualitative outline of descriptive, pertaining, and non-explorative analytical type, to focus in showing the linkage between public, economic, and local economic policy. Results: The Mexico’s economic policy aids the main objective of stabilization process since 1994 to 2024, but that has not been enough in the last five years, obliging to use fiscal policy and conditioning the implementation of local economic policy —acquiring the same or similar features of national economic policy that restrains its implementation—. Conclusions: From a national perspective, it is difficult to describe the design and orchestration of economic policy. But in another framework, from local perspective, the creation of an economic policy doesn’t exist; so, the development of economic policy as well as public policy is void.